Internalization of Ilahiyah and Insaniah Values in Microteaching for Professional Teachers - Zainal Asril; Fathiyah Mohd Fakhruddin; Zainul Arifin; Torkis Lubis (International Islamic Studies Development and Research Center (IISDRC), 2026)
Microteaching plays a crucial role in preparing prospective teachers, as it serves as a platform for integrating theory and practice. However, the internalization of ilahiyah and insaniah values in microteaching has not yet been fully optimized, resulting in limited adaptability among students during teaching practice in schools. This article aims to analyze the urgency of applying ilahiyah and insaniah values in microteaching as a foundation for shaping professional teachers with Islamic character. The study employs a qualitative approach using content analysis, based on literature review, policy documents, and previous studies related to Islamic value-based microteaching. The analysis highlights basic teaching skills integrated with Quranic values such as qaulan sadida (truthful speech), qaulan baligha (impactful words), and qaulan karima (noble words). The findings indicate that the internalization of ilahiyah and insaniah values strengthens pedagogical, social, professional, and personal competencies of prospective teachers. Islamic value-based microteaching not only enhances technical teaching skills but also builds moral, ethical, and spiritual foundations that contribute to teacher professionalism. The implications of this study emphasize that developing microteaching grounded in Islamic values can serve as an effective strategy to improve teacher education quality while addressing regulatory demands and modern curriculum needs.